1994
DOI: 10.1172/jci117561
|View full text |Cite
|
Sign up to set email alerts
|

Dominant clonotypes in the repertoire of peripheral CD4+ T cells in rheumatoid arthritis.

Abstract: Clonal expansion of T cell specificities in the synovial fluid of patients has been taken as evidence for a local stimulation of T cells. By studying the T cell receptor (TCR) repertoire of CD4± T cells in the synovial and peripheral blood compartments of patients with early rheumatoid arthritis (RA), we have identified clonally expanded CD4 + populations. Expanded clonotypes were present in the peripheral blood and the synovial fluid but were not preferentially accumulated in the joint. Dominant single clonot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
85
0
1

Year Published

1995
1995
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(91 citation statements)
references
References 44 publications
(30 reference statements)
5
85
0
1
Order By: Relevance
“…Clonal expansions have been found predominantly in CD8+ T cells studies have shown that clonal expansion can be found in at least 10% of the RA population studied (34). We have also observed clonal expansion of CD4+ T cells in patients with RA (26). These clonal expansions involved only a limited number of clonotypes, and were smaller and less widespread than the clonal expansion we have observed after CAMPATH-1H treatment.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Clonal expansions have been found predominantly in CD8+ T cells studies have shown that clonal expansion can be found in at least 10% of the RA population studied (34). We have also observed clonal expansion of CD4+ T cells in patients with RA (26). These clonal expansions involved only a limited number of clonotypes, and were smaller and less widespread than the clonal expansion we have observed after CAMPATH-1H treatment.…”
Section: Discussionsupporting
confidence: 55%
“…Complementary DNA from CD4+ T cells derived from peripheral blood before and after treatment and derived from synovial tissue after treatment were amplified by PCR with the appropriate Vp-specific primer set (Vp5.l or Vp8, depending on the clonal specificity). The amplified template was dot-blotted onto supported nitrocellulose membranes, immobilized, and prehybridized as described (26). The membranes were then hybridized with a biotinylated Cp probe (ACACAGCGAC-CTCGGGTGGGGA) and probes specific for the junctional polymorphisms of the VpS.…”
Section: Methodsmentioning
confidence: 99%
“…Second, this skewing is a primary event, rather than merely a consequence of inflamma- tion, since the unaffected siblings of RA patients also display expanded T cell clonotypes (46,47). Third, although alterations have been noted in the peripheral compartment (48), they are more pronounced in the joint, are similar in different joints in the same patient, and are stable over time (49,50). Finally, the ability to transfer disease to SCID mice by injection of RA synovial T lymphocytes suggests a pathogenic role for these cells (51).…”
Section: Discussionmentioning
confidence: 99%
“…This might explain stronger in vitro response to CII immunization and development of arthritis in DW4 mice and not in DW10 mice. Recent studies have shown oligoclonal expansion of T cells in periphery and joints of RA patients, which is thought to be driven in part by CII, suggesting that T cells reactive to CII may be mediators of RA pathogenesis (50,51). In double transgenic mice resistant allele is able to modulate the development of arthritis by lower amounts of inflammatory cytokines and increased apoptosis leading to decreased incidence.…”
Section: Discussionmentioning
confidence: 99%